Aesthetic Subunit Reconstruction Facilitated with V-Y Island Advancement Flaps on the Face: A Case Report - Suárez, Jaime Eduardo Pachón (Wolters Kluwer Health, 2014)
SUMMARY: The reconstruction of complex facial soft-tissue defects is a challenge that is often encountered by the plastic surgeon. Careful planning and knowledge of the aesthetic subunits that border the defect are paramount to achieve optimal results. We present a case of a 56-year-old woman who underwent excision of a large disfiguring chronic xanthelasma that extended from canthus to canthus across the nasal bridge. An aesthetic outcome was achieved by use of bilateral V-Y nasolabial flaps combined with a V-Y glabella advancement, which allowed for a tension-free like-for-like subunit reconstruction.